A PENGARUH PERSEPSI HARGA, KUALITAS PRODUK DAN KEPERCAYAAN TERHADAP NIAT BELI SMARTPHONE BEKAS PADA KONTER HANDPHONE SARANG REPAIR DI KOTA BANGUN - Zali, M. ROZALI; Fahleti, Widya Hana; Dewi, Septira (I-Con Media, 2024)
The demand for information that is very fast and easy makes producers engaged in the field of communication make innovations by creating or developing practical communication tools, one of which is creating cellular phones. At this time, the sale of used smartphones has become a fairly large market and continues to grow. Many consumers choose used smartphones as a more affordable alternative compared to buying new products. The purpose of this study is to find out and examine how to manage price perceptions, product quality, and trust to build Intention to Buy Used Smartphones at Sarang Repair Mobile Counters in Kota Bangun. The research data was collected through a questionnaire. The samples studied were 50 respondents. The analytical method used in this study uses Multiple Linear Regression Analysis with hypothesis testing, namely the f-test and t-test.The results of this study indicate that (1) price perception, product quality, and trust have a simultaneous effect on the intention to purchase used smartphones at Sarang Repair  phone counter in Kota Bangun, and this has been accepted and proven to be true. (2) price perception, product quality, and trust have a partial effect on the intention to purchase used smartphones at Sarang Repair phone counter in Kota Bangun, and this has been accepted and proven to be true. And, (3) trust has the most dominant effect on the intention to purchase used smartphones at Sarang Repair phone counter in Kota Bangun, and this has been accepted and proven to be true.